2016
DOI: 10.1534/genetics.115.183244
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/Wingless Pathway Activation Is Promoted by a Critical Threshold of Axin Maintained by the Tumor Suppressor APC and the ADP-Ribose Polymerase Tankyrase

Abstract: Wnt/b-catenin signal transduction directs metazoan development and is deregulated in numerous human congenital disorders and cancers. In the absence of Wnt stimulation, a multiprotein "destruction complex," assembled by the scaffold protein Axin, targets the key transcriptional activator b-catenin for proteolysis. Axin is maintained at very low levels that limit destruction complex activity, a property that is currently being exploited in the development of novel therapeutics for Wnt-driven cancers. Here, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 44 publications
8
56
1
Order By: Relevance
“…Although this may seem somewhat surprising, it is consistent with inactivation of Tnks in Drosophila, which also causes no overt abnormalities (Feng et al, 2014;Wang et al, 2016a and2016b;Yang et al, 2016). Like for Iduna, Tnks mutants have no obvious effects on wing development and the expression of Wingless target genes in larval wing discs, despite the fact that Axin levels are increased (Feng et al, 2014;Wang et al, 2016a and2016b;Yang et al, 2016). Our interpretation of these findings is that most tissues can tolerate relative modest (2-3fold) changes of Axin.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Although this may seem somewhat surprising, it is consistent with inactivation of Tnks in Drosophila, which also causes no overt abnormalities (Feng et al, 2014;Wang et al, 2016a and2016b;Yang et al, 2016). Like for Iduna, Tnks mutants have no obvious effects on wing development and the expression of Wingless target genes in larval wing discs, despite the fact that Axin levels are increased (Feng et al, 2014;Wang et al, 2016a and2016b;Yang et al, 2016). Our interpretation of these findings is that most tissues can tolerate relative modest (2-3fold) changes of Axin.…”
Section: Discussionsupporting
confidence: 72%
“…The Wingless pathway is also involved in adult tissue self-renewal in Drosophila (Lin et al, 2008). Genetic depletion of proteins in the Wingless pathway, such as Tcf, arr, dsh and pygo, leads to inhibition of Wingless signaling activation which in turn causes over-proliferation of stem cells in the Drosophila midgut (Kramp et al, 2002;Wang et al, 2016a and2016b;Tian et al, 2016). However, inactivation of Wnt signaling in the small intestine of mice decreases the proliferative potential of stem cells (Fevr et al, 2007;Korinek et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fas III staining confirmed that the morphology of cells in Apc2 or Apc1 clones was the same as the neighboring wild-type cells (Fig 2M and 2R), indicating that the decreased Axin localization to puncta at the cell periphery was not a secondary consequence of disrupted cell morphology. Importantly, previous genetic and biochemical studies had demonstrated that endogenous Axin is not destabilized as a consequence of Apc loss [16]; therefore, the decreased localization of Axin in peripheral puncta is not secondary to decreased Axin levels in Apc mutant cells. Based on these results, we conclude that Apc promotes Axin localization to puncta at the cell periphery in the unstimulated state.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the efficacy of Tnks inhibitors could reflect an essential function for Tnks in the amplification of pathway activity in Wnt-driven cancers. Depletion of Tnks has no obvious effects on wing development or the expression of Wingless target genes in larval wing discs unless Axin levels are raised above the endogenous level (Feng et al, 2014;Wang et al, 2016). The threshold at which Axin levels inhibit Wingless signaling in wing discs is between 3-and 9-fold above the endogenous Axin level ) and more than 3-fold in embryos .…”
Section: Discussionmentioning
confidence: 99%